Incessant Conflict and the Economic Development of Wukari and Takum Local Government Areas of Taraba State - Umar, Garpiya; Gali, Abdullahi (Kashere Journal of Politics and International Relations, 2025)
This research work examines the impacts of incessant conflict on the economic development of Wukari and Takum Local Government Areas of Southern Taraba State, Nigeria. Different aspects of conflict were examined. These include ethnic, religious, and communal tensions. Conflicts are generally associated with effects on essential economic indicators like infrastructure, investment, agriculture, and human capital. The study adopted a descriptive research design using a qualitative approach in data collection. Data was collected through in-depth interviews from 16 informants, with 8 informants each from Wukari and Takum. Data collected were analysed thematically after transcription. Pluralist and elite theories were used as a theoretical framework for analysis. A thorough review of existing literature was carried out to offer insights into the mechanisms by which conflict impedes developmental efforts in Wukari and Takum. The findings show that engaging government and the local stakeholders, deployment of Security personnel, and rotational chieftaincy approved by the State House of Assembly were among the strategies adopted to curb incessant conflicts in the study areas. The study also reveals that conflict in Wukari and Takum Local Government Areas has affected the economic development of the localities.